EXPERIENCE OF TREATMENT OF A PATIENT WITH POSTOPERATIVE PERINEAL HERNIA (CLINICAL CASE) - Татьяна Владимировна Мироненко; Орлан Валерийович Ооржак; Александр Карлович Лейсле; Татьяна Николаевна Хапаева; Евгений Владимирович Довбета; Александр Андреевич Харитонов; Светлана Ивановна Елгина; Вадим Гельевич Мозес; Елена Владимировна Рудаева; Кира Борисовна Мозес; Яэль Центер (Медицина в Кузбассе)
Chemical burn of the esophagus – local damage to the wall of the esophagus due to accidental or intentional ingestion of a chemical substance of cauterizing action through the mouth. The cause of a chemical burn of the esophagus is accidental or intentional ingestion through the mouth of concentrated solutions of inorganic or organic acids, solutions of alkalis, as well as strong oxidants. Scar tissue that exists for a long time against the background of chronic esophagitis, constantly traumatized by saliva, food masses (with partial patency preserved) in a few years can lead to the development of dysplasia and eventually malignant degeneration (squamous cell carcinoma), the probability of development, which is more than 2 thousand times higher than among people who did not have a burn esophagus. In recent decades, the development of the endoscopic industry and technical equipment, the «gold standard» of conservative treatment of post-burn cicatricial strictures of the esophagus is bougie in various modifications. This article describes two rare clinical cases of esophageal burns with different outcomes.